ANALISIS KONTRIBUSI DAN EFEKTIVITAS PENERIMAAN RETRIBUSI PARKIR TERHADAP PENDAPATAN ASLI DAERAH KOTA MALANG - Putri, Neysa Adelia Nova Abdullah; Galuh, Ajeng Kartika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The purpose of this study is to determine the contribution and effectiveness of the receipt of parking fees to local revenue in Malang in 2015-2022. This research is expected to be used as material for suggestions for local governments to determine the businesses that local governments need to do to encourage increasing parking retribution. In this study, the data analysis method used is a quantitative data analysis method. Based on this study's results, parking fees' contribution to local revenue shows a fluctuating tendency and has an average of 1.29% in the study year. While the effectiveness of parking levies tends to decline in the study year with an average of 96.07%. Receipt of regional levies needs to be at a level in order to increase the effectiveness of parking fees and support the contribution of parking fees to local revenue.